The use of Positive Psychotherapy tools and concepts in the coming out process of a non-heteronormative (LGBTA) client: A case report - Krzysztof Dembinski (The Global Psychotherapist)
This paper explores therapeutic challenges faced by non-heteronormative individuals before coming out, emphasizing the role of Positive and Transcultural Psychotherapy (PPT) in providing support. A primary focus of the therapy for these individuals includes preparing for and managing the coming out process, which is often fraught with stress and fear of rejection. Therapeutic settings may provide the first safe space for coming out, a repeated process rather than a one-time event. Tools such as the Balance model and the Differentiation Analysis Inventory (DAI) are employed to help clients identify and address areas of imbalance and conflict. PPT’s emphasis on Relationships- and Model Dimensions further aids clients in understanding how their relationships and coping mechanisms have been shaped over time, particularly by familial interactions. Through the use of PPT, therapists are equipped to create a supportive environment that addresses the challenges faced by non-heteronormative individuals before coming out.